Efektivitas Timolol 0,5% dalam Menurunkan Tekanan Intraokular dan Meningkatkan Kualitas Hidup Pasien Glaukoma di Klinik Mata Dr. Haryo Bojonegoro: The Effectiveness of 0.5% Timolol in Reducing Intraocular Pressure and Improving the Quality of Life of Glaucoma Patients at Dr. Haryo Eye Clinic, Bojonegoro - Irma Hidayah; Nawafila Februyani; Ainu Zuhriyah (JURNAL FARMASI DAN MAKANAN, 2025)
Glaucoma is one of the leading causes of sensory disability and irreversible blindness worldwide. This study aims to analyze the effectiveness of 0.5% Timolol in reducing intraocular pressure and its impact on the quality of life of glaucoma patients at Dr. Haryo Eye Clinic, Bojonegoro, in 2024. The research method used is the Retrospective-Prospective research method using primary and secondary data, involving 57 patients as samples. The study was conducted in March 2025. Statistical analysis of the effectiveness of 0.5% Timolol was carried out using paired-samples t-test and simple linear regression analysis. The results showed that of the 57 respondents, 47.4% were male and 52.6% were female, with the most common age group being 58–67 years (40.3%). The average percentage of intraocular pressure (IOP) reduction among glaucoma patients using 0.5% Timolol was 9.12%, and it showed an influence in improving quality of life by 17%. The ANOVA test revealed a significance value of 0.001, which is below the alpha significance level of <0.05.The conclusion of this research is 0.5% Timolol is effective in reducing intraocular pressure with an average reduction of 9.12% and has an influence in improving the quality of life of glaucoma patients by 17%.